2017
DOI: 10.1038/s41598-017-06614-0
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Regulates Bone Turnover by Targeting RANKL Expression in Bone Lining Cells

Abstract: Estrogen is critical for skeletal homeostasis and regulates bone remodeling, in part, by modulating the expression of receptor activator of NF-κB ligand (RANKL), an essential cytokine for bone resorption by osteoclasts. RANKL can be produced by a variety of hematopoietic (e.g. T and B-cell) and mesenchymal (osteoblast lineage, chondrocyte) cell types. The cellular mechanisms by which estrogen acts on bone are still a matter of controversy. By using murine reconstitution models that allow for selective deletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
109
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(116 citation statements)
references
References 71 publications
5
109
0
2
Order By: Relevance
“…Studies on the subcellular localization of steroid receptors have demonstrated that they can have effects other than the non-genomic action, thereby revealed their ability to interact with target effectors and activate signaling pathways. Src is involved in the regulation of estrogen receptors, which are known to regulate the homeostasis of a variety of tissues, including the bone [60]. Low levels of estrogen deficiency lead to accelerated bone loss and this is the primary cause of postmenopausal osteoporosis [61].…”
Section: Src and Estrogen Receptormentioning
confidence: 99%
“…Studies on the subcellular localization of steroid receptors have demonstrated that they can have effects other than the non-genomic action, thereby revealed their ability to interact with target effectors and activate signaling pathways. Src is involved in the regulation of estrogen receptors, which are known to regulate the homeostasis of a variety of tissues, including the bone [60]. Low levels of estrogen deficiency lead to accelerated bone loss and this is the primary cause of postmenopausal osteoporosis [61].…”
Section: Src and Estrogen Receptormentioning
confidence: 99%
“…(50) The antiresorptive effects of these drugs are thought to rely on several molecular mechanisms including suppressing stromal cell, osteoblast, and lining cell production of RANKL, increasing osteoblastic production of osteoprotegerin, directly suppressing the production of proresorptive cytokines, and promoting osteoclast apoptosis. (50,51) Like denosumab, the bone turnover suppressive effects of these compounds are rapidly reversible, though a rebound phenomenon is not prominent. (52)(53)(54) Antiresorptive Agents After Anabolic Agents When teriparatide therapy is initiated and sustained, serum and urine markers of bone remodeling generally return to their pretreatment baseline before the end of the 24-month course while BMD continues to increase over the entire treatment period.…”
Section: Antiresorptive Therapiesmentioning
confidence: 99%
“…Estrogens and selective estrogen receptor modulators, primarily acting through its binding to estrogen receptor alpha (ERα), play a key role in both osteoblast and osteoclast biology but in the pharmacologic setting act primarily as antiresorptive agents . The antiresorptive effects of these drugs are thought to rely on several molecular mechanisms including suppressing stromal cell, osteoblast, and lining cell production of RANKL, increasing osteoblastic production of osteoprotegerin, directly suppressing the production of proresorptive cytokines, and promoting osteoclast apoptosis . Like denosumab, the bone turnover suppressive effects of these compounds are rapidly reversible, though a rebound phenomenon is not prominent …”
Section: Introductionmentioning
confidence: 99%
“…Menopause is regularly connected with genuine open issues in moderately aged ladies (Ye et al, 2015). A diminishment in estrogen levels is ordinarily accepted to cause mental and state of mind changes, and also physiological changes that outcome in side effects (Streicher et al, 2017). Accordingly, hormone substitution treatment (HRT) has been used to upgrade menopausal symptoms (Nelson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%